Host switching between native and non‐native trees in a population of the canker pathogen Chrysoporthe cubensis from Colombia. (16th July 2012) - van der Merwe, N. A.; Steenkamp, E. T.; Rodas, C.; Wingfield, B. D.; Wingfield, M. J.
<x xml:space="preserve">Abstract</x> The purpose of this study was to test the hypothesis that Chrysoporthe cubensis on native trees in South America could be the source of the pathogen that causes severe stem cankers and often mortality in commercially propagated Eucalyptus trees. This was done by investigating populations originating from two adjacent Eucalyptus (Myrtaceae) plantations in Colombia, and wild Miconia rubiginosa trees (Melastomataceae) growing alongside these stands. Polymorphic microsatellite markers were used to quantify allele sizes in 20 and 39 isolates from the two Eucalyptus stands and 32 isolates from adjacent M. rubiginosa trees. Gene and genotypic diversities were calculated from these data, and population differentiation and assignment tests were performed to ascertain whether the populations were genetically different. Results showed that there were no differences between any of the populations using these techniques, and that they can be treated as a single population. Therefore, the results support the hypothesis that host switching has occurred in C. cubensis in Colombia.